A simple LC–MS/MS method for determination of kynurenine and tryptophan concentrations in human plasma from HIV-infected patients. (June 2013) - Huang, Yong; Louie, Alexander; Yang, Qiyun; Massenkoff, Nicholas; Xu, Connie; Hunt, Peter W; Gee, Winnie
Background: Indoleamine 2, 3-dioxygenase, catalyzing tryptophan (Trp) metabolism through the kynurenine (Kyn) metabolic pathway, plays important roles in immune suppression and the CNS. In this article, we report a simple, rapid and specific LC–MS/MS method for accurate determination of Kyn and Trp concentrations in human plasma from HIV-infected patients.Results: The human plasma sample (100 µl) was mixed with Kyn-d4 and Trp-d5 internal standards and then precipitated with trifluoroacetic acid. The supernatant was directly analyzed by LC–MS/MS. The assay using surrogate matrix calibrators was validated for precision, accuracy, matrix effect, extraction efficiency and stability. Some assay validation issues for endogenous substance bioanalysis using an LC–MS/MS method are discussed.Conclusion: A simple, specific and reproducible LC–MS/MS method has been developed and validated for measuring Kyn and Trp in human plasma samples.